(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In this article, the factors affecting the formation of altruism and the influence of the educational process on the formation of altruism in students are psychologically analyzed. Gender differences in the manifestation of altruism in a students. Empirical researching on correlation between altruism and will qualities in teenage years. In this article there has been shown analysis of factors in development of altruism and will qualities that connected with altruism. According to research results, altruism is related with will qualities such as responsibility, steadiness, ambitiousness, independence and etc.